Implementation of visa-free visit policy based on Presidential Regulation Number 21 of 2016 concerning Visa-Free Visits for Foreign Nationals - Annisa Rizqi Amalia (Proceedings Series on Social Sciences & Humanities, 2023)
With the beginning of the current era of globalization, there are no more boundaries that can separate one country from another. In order to increase the country's foreign exchange and also improve the working relationship of the Indonesian state with other countries, the Indonesian government enforces the Visa-Free Visit Policy. One form of policy issued by the Indonesian government is outlined in Presidential Regulation Number 21 of 2016 concerning visa- free visits that have been implemented in Indonesia on March 2016 which applies to 169 countries. The purpose of writing this article is to provide information related to the enactment of Presidential Regulation Number 21 of 2016 in Indonesia. In this article there are 2 (two) problems that will be discussed, namely the purpose of the enactment of Presidential Regulation Number 21 of 2016 concerning Visa-Free Visits and the effectiveness of the implementation of Presidential Regulation Number 21 of 2016 concerning Visa-Free Visits in Indonesia. The research method used is the Qualitative method. The results showed that the purpose of the enactment of Presidential Regulation Number 21 of 2016 concerning visa-free visits is to increase the country's foreign exchange, especially in terms of the economy to improve the structure of trade and the impact caused by the existence of this Regulation, namely the abuse of residence permits, document forgery, cyber crime, trafficking in persons, terrorism threats, drug smuggling, and also a decrease in the amount of PNBP every year, so that it has not been maximized in its application in Indonesia. It can be seen that the implementation of Presidential Regulation Number 21 of 2016 concerning Visa-Free Visits in Indonesia has not been effective and the government must review the policy of BVK so that the expected goals can be realized. And also the government must have other strategies to be able to overcome this problem.